Bacterial antigen activation of Vdelta1 and Vdelta2 gammadelta T cells of persons infected with human immunodeficiency virus type 1 - Chervenak, K A; Lederman, M M; Boom, W H (The Journal of infectious diseases, 1997)
Vdelta2 gammadelta T cells are readily activated by microbial antigens. In persons infected with human immunodeficiency virus type 1 (HIV-1), the number of gammadelta T cells remains the same or increases in association with reversal of the Vdelta2/Vdelta1 ratio from > or = 1 to < 1. Vdelta2 T cell responses to microbial antigens were tested in 11 HIV-1-infected (> or = 500 CD4 cells/mm3) and 7 uninfected persons. In persons with HIV-1 infection, Mycobacterium tuberculosis expanded Vdelta2 cells in 1 person as did Salmonella typhimurium in 4; however, Candida albicans antigens did not lead to more Vdelta2 cells. Vdelta2 responses to M. tuberculosis were enhanced by interleukin (IL)-2 in HIV-1-infected persons (from 1 subject to 7; P < .01) and were associated with increased interferon-gamma production. Bacterial antigens and IL-2 increased HIV-1 replication; M. tuberculosis antigens induced the greatest increase. Thus, in HIV-1-infected persons with > or = 500 CD4 cells/mm3, Vdelta2 T cell responses to bacterial antigens remain intact.